STUDIES ON GENETIC DIVERSITY IN Vigna mungo L. Hepper IN YMV HOTSPOT - A.J. NAINU, R. KARTHIKEYAN, R. THIRUMALAI,; S. MURUGAN, V. DIVYABHARATHI, R. NARAYANAN, (Horticultural Biotechnology Research)
The present investigation was conducted to examine the 41 blackgram genotypes along with one check (T-9) to study the genetic diversity. Analysis of variance showed highly significant differences among 41blackgram genotypes for 9 quantitative characters studied. Maximum genotypic and phenotypic variance was recorded for percentage of disease infection, single plant seed yield, and number of pods per plant. Minimum GCV and PCV were recorded for pod length, days to 50% flowering, number of seeds per pod. High heritability was recorded for percentage of disease infection, single plant seed yield, and number of pods per plant. High heritability coupled with high genetic advance as percent of mean was recorded for percentage of disease infection, single plant seed yield. Genetic diversity estimated in 41 blackgram genotypes using Mahalanobis’s D2 statistic. Forty one genotypes were grouped into seven clusters by Tocher method (Mahalanobis Euclidean Distance) cluster analysis. The maximum inter-cluster distance was observed between cluster VI and cluster VII and maximum intra-cluster distance was observed in cluster VI. Cluster VII showed maximum cluster mean value for seed yield per plant. Among all the characters, seed yield per plant and percentage of disease infection contributes maximum.